Konsekuensi Fikih Atas Aborsi Dalam Rangka Percepatan ‘Iddah Hamil - Muda'i, Syaiful; Ulil Albab, Muhammad (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2024)
Islam has established detailed regulations covering all aspects of life, all of which aim at achieving well-being (maslahah). Various life challenges, including issues in family life, have been addressed through Shari'a to provide optimal solutions that are fair to all parties. For example, the implementation of iddah for a woman divorced by her husband or whose husband has passed away while she is pregnant reflects a highly humane approach. This regulation safeguards the rights of the woman, her unborn child, and even the husband who divorced her. Therefore, it is not permissible for a woman in iddah to hastily end her waiting period through means that are inhumane and contrary to Shari’a, such as abortion. Islamic jurists (fuqaha) have expressed diverse opinions regarding the legality and consequences for women who perform abortion solely to expedite the end of their iddah. Some scholars permit abortion if the fetus is under 120 days old and has not yet been ensouled (ruh). In such cases, terminating the pregnancy could be considered as concluding the iddah, provided there is no intention to manipulate the law. Conversely, scholars who categorically prohibit abortion argue that iddah cannot be considered completed in such instances, and the waiting period reverts to the standard calculation based on aqra’ (menstrual cycles) or syuhur (months).